2014
DOI: 10.13005/bbra/1546
|View full text |Cite
|
Sign up to set email alerts
|

Production, Formulation and Application of Seaweed Liquid Fertilizer using Humic Acid on Growth of Arachis hypogaea

Abstract: The aim of the present investigation was to determine the influence of Seaweed Liquid Fertilizer (SLF), Humic acid (HA) and combinations of SLF: HA in various concentrations on the growth of Groundnut (Arachis hypogaea). The above plant growth promoters are applied as foliar spray at an interval of twice in a month with the following concentrations such as SLF (1 to 10%), HA (0.1 to 1%) and SLF:HA (1:0.9% to 9:0.1%). The SLF:HA (6:0.4%) was found to be the most effective formulation with increasing growth of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
1
6
0
3
Order By: Relevance
“…In recent years, limited experimental studies testing the additive and/or synergistic effects of various PBs categories, have demonstrated that combinations of non-microbial PBs or microbial inoculants with HA, SWE, or PH give more reproducible benefits to plant growth and production ( Borges Baldotto et al, 2010 ; Bettoni et al, 2014 ; Nikbakht et al, 2014 ; Prakash et al, 2014 ; Rouphael et al, 2017a ). For instance, groundnut sprayed at biweekly intervals with HA or SWE increased plant height and branching by 34.5 and 33% (for HA) and 17.2 and 60.0% (for SWE), respectively, in comparison to the untreated control treatment, whereas the applications of both PBs together (SWE:HA) exhibited a synergistic interaction with higher increase (65.0 and 100%, respectively) compared to the sum of the independent biostimulant effects (Figure 1 ; Prakash et al, 2014 ). In the same study, improvement in plant growth was associated to the stimulation of N uptake and chlorophyll biosynthesis which may have improved the photosynthetic activity, triggering the translocation of photosynthates to the sinks.…”
Section: Exploiting Synergistic Interactions Among Plant Biostimulantmentioning
confidence: 99%
“…In recent years, limited experimental studies testing the additive and/or synergistic effects of various PBs categories, have demonstrated that combinations of non-microbial PBs or microbial inoculants with HA, SWE, or PH give more reproducible benefits to plant growth and production ( Borges Baldotto et al, 2010 ; Bettoni et al, 2014 ; Nikbakht et al, 2014 ; Prakash et al, 2014 ; Rouphael et al, 2017a ). For instance, groundnut sprayed at biweekly intervals with HA or SWE increased plant height and branching by 34.5 and 33% (for HA) and 17.2 and 60.0% (for SWE), respectively, in comparison to the untreated control treatment, whereas the applications of both PBs together (SWE:HA) exhibited a synergistic interaction with higher increase (65.0 and 100%, respectively) compared to the sum of the independent biostimulant effects (Figure 1 ; Prakash et al, 2014 ). In the same study, improvement in plant growth was associated to the stimulation of N uptake and chlorophyll biosynthesis which may have improved the photosynthetic activity, triggering the translocation of photosynthates to the sinks.…”
Section: Exploiting Synergistic Interactions Among Plant Biostimulantmentioning
confidence: 99%
“…Lastly, synergistic effects could be observed when cumulative effects of BSs exceeded their additive effects; which is ultimately the preferred outcome. In recent years, many studies demonstrated that combined application of microbial and non-microbial BSs generally provided better benefits due to synergistic interactions among the BSs, resulting in enhanced growth, and stress protection [ 24 , 26 , 222 , 223 , 224 , 225 ]. For instance, microbial BSs Trichoderma virens (TG41) with a vegetal biopolymer-based BSs (VBP) enhanced CO 2 assimilation in lettuce and increased mineral contents by 10% for K and 12% for Mg [ 226 ].…”
Section: Exploiting Synergistic Biostimulatory Interactions Among Biostimulantsmentioning
confidence: 99%
“…Het voordeel van mengsels is dat ingrediënten elkaar kunnen versterken (synergistische werking). Bijvoorbeeld toevoeging van zeewierextracten in combinatie met humuszuur toonde een versterking van groeikracht; groter dan toevoeging van de afzonderlijke ingrediënten (Prakash et al 2014). Niettemin is er een gebrek aan kennis over interacties tussen niet-microbiële biostimulanten (Rouphael and Colla, 2018).…”
Section: Mengsels Van Ingrediëntenunclassified
“…Deze interactie-effecten kunnen positief of negatief zijn. Bijvoorbeeld, toevoeging van zeewier extracten in combinatie met humuszuur toonde een versterking van groeikracht; een versterking die groter is dan op basis van toevoeging van de losse ingrediënten (Prakash et al 2014). Interacties tussen micro-organismen in biostimulanten kunnen ook de effectiviteit veranderen.…”
Section: Concentraties Chemische Samenstelling and Interactiesunclassified